Neuron–astrocyte interactions in neurodegenerative diseases: Role of neuroinflammation - Rama Rao, Kakulavarapu V. (Clin Exp Neuroimmunol, 2015)
Selective neuron loss in discrete brain regions is a hallmark of various neurodegenerative disorders, although the mechanisms responsible for this regional vulnerability of neurons remain largely unknown. Earlier studies attributed neuron dysfunction and eventual loss during neurodegenerative diseases as exclusively cell autonomous. Although cell-intrinsic factors are one critical aspect in dictating neuron death, recent evidence also supports the involvement of other central nervous system cell types in propagating non-cell autonomous neuronal injury during neurodegenerative diseases. One such example is astrocytes, which support neuronal and synaptic function, but can also contribute to neuroinflammatory processes through robust chemokine secretion. Indeed, aberrations in astrocyte function have been shown to negatively impact neuronal integrity in several neurological diseases. The present review focuses on neuroinflammatory paradigms influenced by neuron–astrocyte cross-talk in the context of select neurodegenerative diseases.